Chemical Composition,Anti-Inflammatory,Antioxidant and Antimicrobial Activity of Essential Oil from Aerial Parts of Chaerophyllum aromaticum L. from Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2018)
The essential oil obtained by hydrodistillation from the aerial parts of Chaerophyllum aromaticum L. was analyzed by GC and GC/MS. Anti-inflammatory activity was evaluated by lipoxygenase inhibition assay. Antioxidant activity was tested by DPPH method. Antimicrobial activity was carried out using microdilution method against seven bacteria and one fungus. The yield of light yellow-coloured essential oil was 1.1 % Eighteen compounds were identified in oil of the aerial parts representing 99.2 % of the C. aromaticum oil. Sabinene (28.1 %), terpinolene (16.7 %) and gamma-terpinene (16.1 %) were characterized as the main compounds. The oil exhibited remarkable anti-inflammatory activity with an IC50, value of 63.62 +/- 1.26 mu g/ml. The oil at a concentration of 20 mg/mL inhibited DPPH radical by 2.06 %. The oil exhibited moderate antibacterial activity against Staphylococcus aureus ATCC 29213 (MIC: 156 mu g/ml) and Sepidermidis ATCC 12228 (MIC: 625 mu g/ml). The results showed that C. aromaticum essential oil was rich in monoterpene compounds and had moderate antibacterial activity against Staphylococcus strains as well as having significant anti-inflammatory activity.
Keywords: Chaerophyllum aromaticum; essential oil; anti-inflammatory activity; antioxidant activity; antimicrobial activity; MACROPODUM BOISS.; ANTIOXIDANT ACTIVITIES; LEAF EXTRACTS; IRAN; APIACEAE; EXPLOITATION; MACROSPERMUM; FRUITS; PLANTS